Correlating rheological properties and printability of collagen bioinks: the effects of riboflavin photocrosslinking and pH. (5th July 2017) - Diamantides, Nicole; Wang, Louis; Pruiksma, Tylar; Siemiatkoski, Joseph; Dugopolski, Caroline; Shortkroff, Sonya; Kennedy, Stephen; Bonassar, Lawrence J
Abstract: Collagen has shown promise as a bioink for extrusion-based bioprinting, but further development of new collagen bioink formulations is necessary to improve their printability. Screening these formulations by measuring print accuracy is a costly and time consuming process. We hypothesized that rheological properties of the bioink before, during, and/or after gelation can be used to predict printability. In this study, we investigated the effects of riboflavin photocrosslinking and pH on type I collagen bioink rheology before, during, and after gelation and directly correlated these findings to the printability of each bioink formulation. From the riboflavin crosslinking study, results showed that riboflavin crosslinking increased the storage moduli of collagen bioinks, but the degree of improvement was less pronounced at higher collagen concentrations. Dots printed with collagen bioinks with riboflavin crosslinking exhibited smaller dot footprint areas than those printed with collagen bioinks without riboflavin crosslinking. From the pH study, results showed that gelation kinetics and final gel moduli were highly pH dependent and both exhibited maxima around pH 8. The shape fidelity of printed lines was highest at pH 8–9.5. The effect of riboflavin crosslinking and pH on cell viability was assessed using bovine chondrocytes. Cell viability in collagen gels was found to decrease after blue light activated riboflavin crosslinking but was not affected by pH. Correlations between rheological parameters and printability showed that the modulus associated with the bioink immediately after extrusion and before deposition was the best predictor of bioink printability. These findings will allow for the more rapid screening of collagen bioink formulations.